Case Report: Unilateral Sixth Cranial Nerve Palsy Associated With COVID-19 in a 2-year-old Child - Knoflach, Katrin; Holzapfel, Eva; Roser, Timo; Rudolph, Lieselotte; Paolini, Marco; Muenchhoff, Maximilian; Osterman, Andreas; Griese, Matthias; Kappler, Matthias; von Both, Ulrich (Frontiers in Pediatrics, 2021)
Children have been described to show neurologic symptoms in acute coronavirus disease 2019 (COVID-19) and multisystemic inflammatory syndrome in children (MIS-C). We present a 2-year-old boy’s clinical course of unilateral acute sixth nerve palsy in the context of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. Onset of the palsy occurred seven days after symptoms attributed to acute infection had subsided. SARS-CoV-2 specific IgG was detected in serum as well as in cerebrospinal fluid. The patient showed a prolonged but self-limiting symptomatic course with a recovery after three and a half months. This case illustrates in a detailed chronological sequence that sixth cranial nerve involvement may occur as post-infectious but self-limiting complication of pediatric SARS-CoV-2-infection thus expanding the neurological spectrum of symptoms for children with COVID-19. Clinicians should be aware of the possibility of post-infectious sixth nerve palsy related to SARS-CoV-2-infection particularly in view of recent respiratory tract infection or confirmed cases of SARS-CoV-2-infection amongst the patient’s close contacts.